An Identity Driven Escalation of Commitment to Negative Spillovers - Mikhaeil, C.; Baskerville, Richard (2018)
The technological advances of the World Wide Web led it to become a highly interactive medium on which billions of individuals share not only their information but also their thoughts and beliefs. While it is an ideal tool to bring people together and expand horizons by connecting remote communities, sadly it is also dangerously effective in spreading diseases or hate crime. Such poor awareness on how such paradoxical outcomes arise is a societal challenge. This conceptual paper focuses on concealable stigmatized identities; i.e., culturally devalued identities that are not visible to others. When acted upon they produce socially questionable activities that incur social penalties and generate (tangible and intangible) societal costs. We explain how cognitive dissonance about one’s identity refines our current understanding of the relationship between (increased) Internet access and (increased) societal negative spillovers. We offer a process model explaining how online escalation-of-commitment leads to offline negative spillovers.